Development of simulation model of a hospital for robotic simulation in ros - Koh, Ling Xian (2022)
The outbreak of novel coronavirus disease 2019 (COVID-19) causes the healthcare workers to face an extremely high risk of getting infected as they need to interact with many different patients. Therefore, it indicates the importance of applying autonomous delivery robots within the hospital as it can help to reduce the contact between the healthcare workers and patients. It requires the robots to be tested and debugged in a reliable simulation environment before it can be tested in a real environment. A key problem in this area is the lack of simulation environment for hospital in Malaysia for the purpose of robotic simulation. Therefore, this project aims to develop a simulation model of a hospital for robotic simulation in Robot Operating System (ROS). A hospital inspection has been conducted to collect relevant information. Then, the simulation model of hospital is developed by using Gazebo, and connected with ROS 2 for robotic simulation purpose. In general, it is proven that simple robotic simulation such as mapping can be conducted smoothly in the developed simulation model.